An Investigation of the correlation between Distributive Justice and Employee Performance considering the Mediating character of Career Incentives: A case study ofCall center industry of Pakistan - Dr. Junaid Athar Khan; Ms. Sourat Mehr; Dr. Naseeb Ullah Shah; Muhammad Saleem Qazi (Journal of Business & Tourism, 2021)
This paper is unique foe being among the few research studies that investigated the impact of distributive justice on employee’s performance considering the mediating aspect of economic benefits or career incentives. For this study, 120 call center employees were randomly selected as the participants of this study however, only 112 responses were assumed reliable and trustworthy for further investigation. For the selection of the participants 10 call centers were selected randomly that are operating in the twin – cities (RWP-ISB) of Pakistan. Various analysis including Hierarchical regression, descriptiveand correlation analysis were employed for the investigation of data and for hypothesis testing. Upon the evaluation of the overall findings of this study, A strong positive correlation is discovered between distributive justice and employee’s performance. Furthermore, a mediating role of economic benefits or career incentives have been discovered on the relationship between distributive justice and employee’s performance. For future research, it is suggested that the researchers should take into account both the organizational features and individual characteristics to get an insight to the the influence of career incentives over performance of employees in an organization. In this regard, an organization should implement a tremendously competitive and effective compensation plan and an attractive remuneration package and some additional employee’s incentivesprograms in proximity with the supreme procedures of distributive justice to accomplish long term and consistent sustainability to get desired level of performance.